PENGEMBANGAN BAHAN AJAR GAMIFIKASI PADA MATERI LIMIT FUNGSI DAN TURUNAN KELAS XI SMAN 13 GOWA - Wahyu Anggraeni; Sri Sulasteri; A. Sriyanti; Nur Yuliany (IKIP Siliwangi, 2022)
This research was carried out with the aim of producing gamification teaching material products for limiting functions and class IX derivatives that met the feasibility criteria, namely valid, practical, and effective. This research is a development research using the ADDIE development model. The stages of the ADDIE development model consist of analysis, design, development, implementation, and evaluation. Product feasibility assessment using validation sheet instruments, student response questionnaires and teacher response questionnaires, as well as learning outcome tests. The collected data were analyzed by qualitative and quantitative descriptive analysis. The research results obtained are: (1) Valid, the average validation results for teaching materials, rpp, student and teacher response questionnaires and learning outcomes tests are 4.66 which are categorized as valid because they are in the range of 4≤V_a<5. (2) Practical, based on the teacher response questionnaire with an average result obtained of 91.66% and the student response questionnaire of 91.25% is in the range of 85% ≤R_G≤100% so that the teacher and student response questionnaire is categorized as very Positive. (3) Effective, the results of the student learning outcomes test analysis were obtained by 80% classically complete and were in the high category. Thus, it was concluded that the gamification teaching materials on the function limit materials and class XI derivatives met the criteria of valid, practical, and effective.